ANTIOXIDANT AND SGC-7901 CELL INHIBITION ACTIVITIES OF RHIZOMA DIOSCOREAE BULBIFERAE. ETHANOL EXTRACTS - Chen, Xiang; Wu, Shu-hui; Zeng, Xiao-bing; Jiang, Xu-wei; Chen, Xiao-ping; Yuan, Jie; Lu, Bao-hua; Li, Jie (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this research was to study the pharmacology of Dioscorea bulbifera L. on antioxidant and anticancer activity. Alcohol extracts of Dioscorea bulbifera L. were made out by different concentration alcohol; they were tested by Hydroxyl radical scavenging test, reducing capacity test and total antioxidant capacity test. In the anticancer test, MTT test was used to study the inhibition rate. The results told that 70% ethanol extracts could scavenge most DPPH• at 2mg/ml. The rate was 55.2%; 80% ethanol extract could clear the most •OH. The clearance rate was 51.2%. 80% ethanol crude extracts possessed the strongest reducing ability per gram of the extract equal to 49.3μmol Fe2 +. Different concentrations of the extracts could inhibit the proliferation of line SGC-7901, and with the concentration increased, the inhibition rate was gradually increased.